A Comparative Review of the Death Penalty Provisions in Pakistan’s Penal Code - Khan, Abzahir; Khan, Astraj (Journal of Islamic and Religious Studies, 2016)
Law plays a pivotal role in the establishment of any peaceful society.islam, being proactive, devised important rules about 1400 years back for the safety of Deen, life, wealth, wisdom and Generation. Qatal (murder) is a crime of taking soul of a humanbeing, about which Islam has announced Qisas i.e to do with assissinater what he has done it to killed human being. In the same manner Pakistan penal Code has gathered rules about crimes steped out in Pakistan. So Pakistan penal code, under several sections has the same punishment. This artcle throws light on Pakistan penal code sections about death Senctance in perspective of Islamic imperium, order and explanation.